Have License, Will Travel: An Analysis of the New ABA Multijurisdictional Practice Rules - Cynthia L. Fountaine (Washington University Law Quarterly, 2003)
Multijurisdictional practice (“MJP”)—that is, law practice in a host state by an out-of-state lawyer who is licensed in a different home state—raises two primary issues: (1) is the out-of-state lawyer violating the host state’s unauthorized practice of law (“UPL”) regulations; and (2) if the lawyer is permitted to practice in the host state, what ethical rules must the lawyer follow while carrying out the work in the host state? These issues are even more complicated by issues of whether or not litigation is pending, and if so, whether it is pending in state or federal court. ABA Model Rules of Professional Conduct (“Model Rules”) 5.5 and 8.5 are designed to regulate MJP. Recognizing important deficiencies in these rules, the ABA recently adopted significant amendments. The primary goals of the amendments are formally to recognize the cross-border nature of modern law practice and to promote uniform rules that will enable lawyers to accurately predict the limits of their authority to represent their clients’ cross-border interests. First, this Article will describe some of the shortcomings of the old Model Rules in regulating MJP. Second, the Article will introduce and explain the new rules governing MJP. The Article will conclude that the amendments succeed in recognizing the realities of modern cross-border law practice and in providing a more effective model framework for MJP regulation, but the amendments do not fully achieve the ABA’s central goal of creating uniform rules that will ensure predictability in MJP.
Keywords: Multijurisdictional practice; Legal ethics; Unauthorized practice of law; A.B.A. Model Rules of Professional Conduct; California; New York; United States; American Bar Association